Порівняльна оцінка методів корекції регіонарної гемодинаміки у комплексному лікуванні хворих із cиндромом діабетичної стопи - Каніковський, О. Є.; Сандер, С. В.; Андросов, С. І.; Рубан, М. М. (Clinical Endocrinology and Endocrine Surgery, 2009)
Efficiency estimation of using of ozonotherapy in 138 patiens with of diabetic foot syndrom was made. Early and remote results of treatment were better. During a 5-year follow-up degree and duration of worsening developed more slouly. Malleolar-humeral index decreased in averige on 20% (in control grup — on 35%), rheography index — on 35% (in control group — on 55%), wolk distance — on 50% (in control group — on 70%). Gangrenous changes of various spread appeared in 38% patiens (in control group — 82%). High amputations frequancy was 15% (in control group — 34%).